Magnetically recoverable Fe3O4 nanocatalyst for the synthesis of biodynamically significant 1H-pyrazolo[1,2-b]phthalazine-5,10-diones derivatives and its DFT study - Ansari M.D.; Sagir H.; Yadav V.B.; Yadav N.; Verma A.; Shakya S.; Singh M.; Siddiqui I.R. (My University, 2025)
An environmentally sustainable and proficient method is reported for the synthesis of medicinally important pyrazolo[1,2-b] phthalazine dione derivatives by aqueous micellar medium catalysed by Fe3O4 NPs. Dialkyl acetylenedicarboxylate with isocyanides in the presence of phthalhydrazide is used as starting material. The main advantages of this protocol are the availability of starting materials, short reaction times, green solvents and practical simplicity. Graphical abstract: [Figure not available: see fulltext.]. © 2022, The Author(s), under exclusive licence to Springer Nature Switzerland AG.